1994
DOI: 10.1093/jac/34.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Multiple dose pharmacokinetics of an oral solution of itraconazole in autologous bone marrow transplant recipients

Abstract: The pharmacokinetics of itraconazole oral solution were measured in seven patients receiving chemotherapy followed by autologous bone marrow transplantation for leukaemia or lymphoma. Patients received 5 mg/kg/day itraconazole either as a once or twice daily dose. Drug concentrations reached steady state by day 15, in both groups. The mean pre-dose itraconazole serum concentration at hour 0, day 8 was 385 ng/mL in the od group and 394 ng/mL in the bd group, rising to 762 and 845 ng/mL by day 15, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 0 publications
2
50
1
1
Order By: Relevance
“…However the number of patients still in the study at these phases is not sufficient to draw a final conclusion on the role of mucositis on itraconazole oral solution absorption. Nevertheless, severity of mucositis could explain the discrepancies observed between some results obtained in the Prentice trial 12 and in our series.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…However the number of patients still in the study at these phases is not sufficient to draw a final conclusion on the role of mucositis on itraconazole oral solution absorption. Nevertheless, severity of mucositis could explain the discrepancies observed between some results obtained in the Prentice trial 12 and in our series.…”
Section: Discussioncontrasting
confidence: 94%
“…Prentice et al 12 have shown that relatively high serum concentrations of itraconazole (C min 394 Ϯ 110 ng/ml and C max 723 Ϯ 217 ng/ml after 8 days of treatment for six patients) can be achieved in bone marrow autograft recipients receiving oral itraconazole solution administered at 2.5 mg/kg twice daily dosages. However this trial differs from ours by the fact that itraconazole treatment was given twice daily, started 3 days after the day of transplant and that the conditioning regimen did not include TBI, inducing probably less vomiting and mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 A recent study in neutropenic children suggests that higher plasma concentrations may be achieved than in adults (mean concentrations Ͼ250 ng/ml were achieved after 3 days in 6-14-year-olds and after 5 days in children under 5 who received 5 mg/kg/day of itraconazole oral solution 19 ). An earlier study had found that plasma levels Ͻ250 ng/ml were associated with prophylaxis failure.…”
Section: Discussionmentioning
confidence: 99%
“…6 Itraconazole has a broader spectrum of activity and is active against both Candida and Aspergillus 7 but the capsule formulation has unpredictable absorption, 8,9 is inconvenient to administer to young children and may be difficult for patients with mucositis to swallow. An oral solution of itraconazole with better bioavailability than the capsules 10,11 is now available and has recently been licensed for use as prophylaxis against deep fungal infections in adult patients with neutropenia. Results from a randomised study in adult neutropenic patients suggest that itraconazole solution provides greater protection than fluconazole against fatal Aspergillus infection.…”
mentioning
confidence: 99%
“…W ith the current formulation, serum concentra tions of itraconazole should be determined regu larly, especially in patients suffering cytotoxic therapy-induced mucosal damage or when ant acids are coadministered. At present, a new for mulation of itraconazole suspended in cyclodextrin solution is being investigated and appears to be better absorbed (35). Other concerns about it raconazole have been identified: the induction of resistance to amphotericin B by previous exposure to itraconazole (36); the possible induction or in hibition of hepatic enzymes by itraconazole; the in teraction of itraconazole with cyclosporine; and the propensity of itraconazole to increase intracel lular levels of cytotoxic drugs such as vincristine and anthracyclines, which might enhance the tox ic effects of these agents.…”
Section: Old Infections Even Though the Azoles And Pomentioning
confidence: 99%